Biomarkers predictive value for early diagnosis of Stroke‐Associated Pneumonia - Zapata‐Arriaza, Elena (Ann Clin Transl Neurol, 2019)
To confirm the diagnostic accuracy of candidate biomarkers in stroke‐associated pneumonia (SAP), we prospectively enrolled ischemic stroke patients with NIHSS ≥ 10 on admission from March‐2016 to August‐2017. Blood samples were collected at baseline, 24 and 48 h after stroke onset. Biomarkers (MR‐proADM, suPAR, SAA) were determined by immunoassays. Regarding biomarkers, MR‐proADM at 24 h (P = 0.04) and both suPAR and SAA at 48 h (P = 0.036 and P = 0.057) were associated with pneumonia. The combination of SAA > 25.15 mg/dL and suPAR> 3.14 ng/mL at 48 h had 80% sensitivity and 95.8% specificity when both biomarkers were above the cut‐off. The evaluated biomarkers represent promising tools to be evaluated in future large, prospective studies on SAP. An accurate SAP diagnosis by thorax CT might help to reduce variability in such studies.